The significance of Mathematics Education under the concept of mathematics culture - Xilian Fu (IJRDO- Journal of Educational Research, 2020)
From the perspective of mathematics culture, we can not only change the traditional view of mathematics, but also form the corresponding view of mathematics education. Mathematics education under the concept of mathematics culture contributes to the unity of mathematics science education goal and humanities education goal.Therefore,the comprehensiveness of classroom teaching content can be realized and students' creative ability can be cultivated.